MENINGKATKAN PEMAHAMAN KONSEP BADAN USAHA DALAM PERKONOMIAN INDONESIA DENGAN MODEL PEMBELAJARAN GROUP INVESTIGATION - Yurnalia, Yurnalia (Lentera: Jurnal Ilmiah Kependidikan, 2020)
Most of the students in class X do not understand the learning material for business entities in the Indonesian economy (Indonesian economic sectors). This is demonstrated by the difficulty in distinguishing between privately owned companies (BUMS) and state-owned enterprises (BUMN). Some of them are still unable to distinguish between business entities and companies. There are even some students who have not been able to distinguish between Village Unit Cooperatives (KUD) and cooperatives in general. The purpose of this study is to improve understanding of the concept of business entities in the Indonesian economy using cooperative learning with the Group Investigation model. The design of this research activity is an action research which consists of two cycles, in which each cycle includes planning, implementation, observation, and reflection. The data collection instruments in this study were a test at the end of each cycle and the teacher's and students' observation sheets. The results of research on student activity in cycle I, 64% in cycle II have increased by 76.33% including in the very active category. Completeness of cycle 1 was 76.25, individual completeness of 25 students was complete and 11 students had not completed it with a completeness percentage of 70%. In cycle 2 it increased by an average of 78.58, 27 students completed individual completeness and 9 students had not completed with a completeness percentage of 75%. Thus, there is an increase in student learning motivation followed by an increase in student learning outcomes with cooperative learning with the Group Investigation model.